Sistem Kompensasi dalam Meningkatkan Kinerja Pendidik : Studi Kasus SDN 014687 Rawang Pasar IV - Khafsah Situmorang; Ropida Batubara; Wahyu Ningsih; Nurhasanah Nasution (Universitas Muhammadiyah Enrekang, 2022)
The background of this research is that to carry out teaching and learning activities in a school, an educator is needed. Educators are the main determinants of the success of the learning process carried out. The performance of a teacher can be well reflected if the results of the teacher's performance can be well appreciated. Compensation is one of the external factors that can improve teacher performance. One of the things that can improve teacher performance is the provision of compensation in the form of salaries, bonuses, types of allowances and other facilities. The provision of compensation is one of the means of stimulants in growing enthusiasm and enthusiasm for work. By building a good compensation system, teacher performance can be improved. Therefore, educational institutions need to pay attention to the compensation system as an effort to improve teacher performance which can have an impact on improving educational services for students. The approach used in this research is a qualitative approach with the type of research used is a case study. With data collection procedures using: in-depth interviews, and observation. Data analysis used is data collection, data presentation and conclusion drawing.